Improved electrochemical activity of Bi0.5Sr0.5FeO3-δ–Ce0.9Gd0.1O1.95composite cathode electrocatalyst for solid oxide fuel cells. Issue 1 (1st January 2021) - Gao, Juntao; Li, Qiang; Guo, Miaomiao; Sun, Liping; Huo, Lihua; Zhao, Hui
Abstract: Developing MIEC materials with high electrocatalytic performance for the ORR and good thermal/chemical/structural stability is of paramount importance to the success of solid oxide fuel cells (SOFCs). In this work, high-activity Bi0.5 Sr0.5 FeO3- δ - x Ce0.9 Gd0.1 O1.95 (BSFO- x GDC, x  = 10, 20, 30 and 40 wt%) oxygen electrodes are synthesized, and confirmed by XRD, SEM and EIS, respectively. The crystal structure, microstructure, electrochemical property and performance stability of the promising BSFO- x GDC composite cathodes are systematically evaluated. It is found that introducing GDC nanoparticles can obviously improve the electrochemical property of the porous composite electrode. Among all these composite cathodes, BSFO-30GDC composite cathode shows the best ORR activity. The peak power density of anode supported single cells employing BSFO-30GDC composite cathode reaches 709 mW cm −2 and the electrode polarization resistance ( R p ) of the BSFO-30GDC is about 0.14 Ω cm 2 at 700 °C. The analysis of the oxygen reduction kinetic indicates that the major electrochemical process of the GDC-decorated composite cathode is oxygen adsorption-dissociation. These preliminary results demonstrated that BSFO-30GDC is a prospective composite cathode catalyst for SOFCs because of its outstanding ORR activity.